2019
DOI: 10.1302/2058-5241.4.180085
|View full text |Cite
|
Sign up to set email alerts
|

Kneeling ability after total knee replacement

Abstract: Kneeling ability is consistently the poorest patient-rated outcome after total knee replacement (TKR), with 60–80% of patients reporting difficulty kneeling or an inability to kneel. Difficulty kneeling impacts on many activities and areas of life, including activities of daily living, self-care, leisure and social activities, religious activities, employment and getting up after a fall. Given the wide range of activities that involve kneeling, and the expectation that this will be improved with surgery, probl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Our study further elaborates on this finding to provide evidence that the initial improvement in patient-reported pain, function, stiffness and knee-related quality of life mainly occurs in the first three months after surgery. While satisfaction ratings were high after TKR, little improvement was observed in activity levels and kneeling ability after surgery, which supports findings from previous studies [8,27] and highlights the need for research to evaluate interventions to improve these outcomes. The 10-year Kaplan-Meier survivorship with all-cause revision as the endpoint for the Triathlon TKR of 95.4% (95% confidence interval 91.8-97.5) is consistent with revision rates reported in the National Joint Registry (3.4%; 95% confidence interval 3.2-3.6) [1] and Australian Orthopaedic Association National Joint Replacement Registry (3.8%; 95% confidence interval 3.6-4.0) [28], and survivorship rates in the Finnish Arthroplasty Register (94%; 95% confidence interval 93-95) [29].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Our study further elaborates on this finding to provide evidence that the initial improvement in patient-reported pain, function, stiffness and knee-related quality of life mainly occurs in the first three months after surgery. While satisfaction ratings were high after TKR, little improvement was observed in activity levels and kneeling ability after surgery, which supports findings from previous studies [8,27] and highlights the need for research to evaluate interventions to improve these outcomes. The 10-year Kaplan-Meier survivorship with all-cause revision as the endpoint for the Triathlon TKR of 95.4% (95% confidence interval 91.8-97.5) is consistent with revision rates reported in the National Joint Registry (3.4%; 95% confidence interval 3.2-3.6) [1] and Australian Orthopaedic Association National Joint Replacement Registry (3.8%; 95% confidence interval 3.6-4.0) [28], and survivorship rates in the Finnish Arthroplasty Register (94%; 95% confidence interval 93-95) [29].…”
Section: Discussionsupporting
confidence: 81%
“…Although many patients have good outcomes after TKR, approximately 20%-30% of patients report long-term pain, functional limitations and dissatisfaction with the outcome of their surgery [5][6][7]. Also, difficulty with more challenging activities, such as kneeling, are common [8]. To meet the growing expectations of patients and to optimise outcomes, manufacturers are continually developing new prosthetic designs.…”
Section: Introductionmentioning
confidence: 99%
“…These findings are consistent with the importance of kneeling to the performance of many daily activities, some occupations, and many religious and cultural observances (e.g., prayer) (33). However, research to date indicates that 60-80% of primary TKA patients report difficulty or an inability to kneel after TKA (34)(35)(36)(37)(38)(39)(40). Identified barriers to kneeling post-TKA include pain and other sensory changes (e.g., numbness around the incision, patient fear of harming the prosthesis, and lack of information about kneeling after TKA).…”
Section: Discussionmentioning
confidence: 99%
“…Of the 26 included studies, only 27% reported consecutive selecting their cohort. Given that only 20% of TKR patients achieve kneeling [48], it is likely that most of the patients included in these studies were high performing and selected for their kneeling ability.…”
Section: Discussionmentioning
confidence: 99%